Global intelligence oversight : governing security in the twenty-first century - Goldman, Zachary K.; Rascoff, Samuel James; Harman, Jane (New York, NY : Oxford University Press, 2016)
'Global Intelligence Oversight' is a comparative investigation of how democratic countries can govern their intelligence services so that they are effective, but operate within frameworks that are acceptable to their people in an interconnected world.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: Intelligence service -- Law and legislation; National security -- Law and legislation; Internal security; Legislative oversight; Law; Laws of specific jurisdictions & specific areas of law